Nephrotoxicity evaluation of 3-monochloropropane-1, 2-diol exposure in Sprague-Dawley rats using data-independent acquisition-based quantitative proteomics analysis. (1st March 2022) - Jin, Chengni; Min, Fenyi; Zhong, Yujie; Sun, Dianjun; Luo, Ruilin; Liu, Qi; Peng, Xiaoli
Highlights: The rat renal alternations caused by administration of 30 mg/kg/day 3-MCPD for 28 days. DIA-MS method was an efficient tool to unravel the toxicity mechanism of 3-MCPD. 3-MCPD led to alterations in proteins related to metabolic pathway and oxidative phosphorylation. Apoptosis and autophagy were involved in the development of 3-MCPD-induced nephrotoxicity. Abstract: 3-Monochloropropane-1, 2-diol (3-MCPD), as a heat-induced food process contaminant, possesses strongly toxic effect on kidney. The present study focuses on characterizing the proteome and clarifying the underlying molecular regulatory mechanisms in a model of kidney injury in rats treated with 3-MCPD. Data-independent acquisition (DIA)-mass spectrometry (MS) based proteomics was used to identify dysregulated proteins in kidney tissues of Sprague-Dawley (SD) rats treated with 30 mg/kg/day 3-MCPD by gavage for 28 days. It was found that a total of 975 proteins were deregulated after 3-MCPD treatment. Bioinformatic analyses revealed that several enzymes related to the metabolisms of amino acid, lipid and carbohydrate in endogenous metabolism were altered in response to 3-MCPD treatment. Moreover, some proteins involved in these pathways were also changed, mainly including oxidative stress, oxidative phosphorylation, apoptosis and autophagy. Our study unravels the vital roles of loss of mitochondrial homeostasis and function and cell death pathways in the development of renal damage induced by 3-MCPD, which provides further valuable insights into the initiation and resolution of 3-MCPD nephrotoxicity. The proposed DIA-MS workflow not only provides a choice for proteomic analysis in toxicological research, but also provides a more comprehensive understanding of the molecular mechanisms of nephrotoxicity induced by toxins.